A hybrid substrate integrated waveguide and spoof surface plasmon polariton leaky‐wave antenna with open stopband suppressed. Issue 11 (2nd September 2020) - Xu, Shen‐Da; Liu, Li; Guan, Dong‐Fang; Hong, Ren‐Tang; Xu, Hantao; Lin, Mingtuan; Yong, Shao‐Wei
Abstract: In this paper, an asymmetric sinusoidal modulated substrate integrated waveguide‐spoof surface plasmon polariton (SIW‐SSPP) leaky‐wave antenna with open stopband suppressed is proposed. The SSPP transmission line can covert the guided waves to the leaky‐wave radiations with frequency‐scanning properties due to the sinusoidal modulation. Using asymmetric model is an effective method to restrain the open stopband. The asymmetric radiating element with π/2 phase difference between the upper and lower sides of the top surface is introduced in the antenna to realize zero‐crossing beam scanning and unidirectional radiation characteristic. In the operating band of 12.6 to 13.7 GHz, the measured scanning angle of the fabricated antenna is from −14° to +34°. The gain is above 10.1 dBi and the radiation efficiency is basically above 50% over the operating band. Although the way of eliminate the open stopband has been proposed, this is the first time it is used in SIW‐SSPP antenna design. It has potential applications in radar and wireless communication systems for simple structure, low‐profile, zero‐crossing beam scanning, and unidirectional radiation performance.